The Selection of Ornamental Plant for Landscape Design of Pollination Garden at Bogor Botanic Gardens - Peniwidiyanti Peniwidiyanti; Irvan Fadli Wanda; Dipta Sumeru Rinandio; Prima Wahyu Kusuma Hutabarat; Muhammad Rifqi Hariri; Dwi Setyanti (UIN Sunan Gunung Djati Bandung, 2020)
Bogor Botanic Gardens is one of the outstanding green areas in Bogor City. Thousands of plant species are growing and providing suitable habitats and feed for various pollinators, such as butterflies, bees, and wasps. A well-designed pollination garden will benefit the pollinators and also create an educational facility for the community. This study aimed to select and characterize species of flowering plants that effectively attract pollinators, particularly Lepidoptera and Hymenoptera, in the pollination garden candidate area. The observa-tion had been carried out on 12 ornamental plant species: Pennisetum purpureum, Cosmos sp., Pachystachys lutea, Cuphea hyssopifolia, Orthosiphon aristatus, Lantana camara, Citrus aurantifolia, Buddleja davidii, Ixora javanica, Nerium oleander, Hibiscus rosa-sinensis, and Aglaia odorata. The method for observing pollinators was a standard walking method. Pollinator photos, its number, its visit time, and the plants it visited were recorded. A total of 23 species of Lepidoptera (20 species from 4 families and 3 species were unidentified) and 9 species of Hymenoptera (4 families) were found in the area with the best obser-vation time at 08.30-09.30 (GMT+7). The most visited plants by pollinators were Cuphea hyssopifolia, Lantana camara and Orthosiphon aristatus. Lepidoptera and Hymenoptera preferred blue-purple and bright-orange-yellow flowers. In addition, the flower characters that might influence pollinator visits are also described. The result would be an essential recommendation for plant selection, landscape design, and construction of the pollination garden in Bogor Botanic Gardens.